Analysis of periplasmic sensor domains from Anaeromyxobacter dehalogenans 2CP‐C: Structure of one sensor domain from a histidine kinase and another from a chemotaxis protein. Issue 5 (30th July 2013) - Pokkuluri, P. Raj; Dwulit‐Smith, Jeff; Duke, Norma E.; Wilton, Rosemarie; Mack, Jamey C.; Bearden, Jessica; Rakowski, Ella; Babnigg, Gyorgy; Szurmant, Hendrik; Joachimiak, Andrzej; Schiffer, Marianne
Abstract Anaeromyxobacter dehalogenans is a δ‐proteobacterium found in diverse soils and sediments. It is of interest in bioremediation efforts due to its dechlorination and metal‐reducing capabilities. To gain an understanding on A. dehalogenans' abilities to adapt to diverse environments we analyzed its signal transduction proteins. The A. dehalogenans genome codes for a large number of sensor histidine kinases (HK) and methyl‐accepting chemotaxis proteins (MCP); among these 23 HK and 11 MCP proteins have a sensor domain in the periplasm. These proteins most likely contribute to adaptation to the organism's surroundings. We predicted their three‐dimensional folds and determined the structures of two of the periplasmic sensor domains by X‐ray diffraction. Most of the domains are predicted to have either PAS‐like or helical bundle structures, with two predicted to have solute‐binding protein fold, and another predicted to have a 6‐phosphogluconolactonase like fold. Atomic structures of two sensor domains confirmed the respective fold predictions. The Adeh_2942 sensor (HK) was found to have a helical bundle structure, and the Adeh_3718 sensor (MCP) has a PAS‐like structure. Interestingly, the Adeh_3718 sensor has an acetate moiety bound in a binding site typical for PAS‐like domains. Future work is needed to determine whether Adeh_3718 is involved in acetate sensing by A. dehalogenans.